Chemical Mechanical Polishing of GaSb Wafers for Significantly Improved Surface Quality - Yan, Bing; Liang, Hongyu; Liu, Yongfeng; Liu, Weihua; Yuan, Wenhui; Zhang, Bingjie; Huang, Li (Frontiers in Materials, 2021)
Gallium antimonide (GaSb) is considered an ideal substrate for heterostructure growth by molecular beam epitaxy. A significant aspect that inhibits the widespread application of infrared plane arrays detector growth on GaSb is the starting substrate surface quality. In this study, the chemical mechanical polishing of GaSb wafers is investigated by considering the effects of the polishing pad, polishing solution, polishing time and pH buffer on their surface morphology and roughness. The surface morphologies and root mean square (RMS) roughness of the free-standing wafers are characterized using a white light interferometer, a laser interferometer and an atomic force microscope. X-ray tomography is employed to measure the surface crystalline quality and strain defects of the samples subjected to the polishing treatments. The results show that with the optimum polishing condition, the polished GaSb wafers demonstrate high-quality surfaces without haze, scratches or strain defect regions. The peak to valley value is 5.0 μm and the RMS roughness can be controlled at less than 0.13 nm. The buffer layer grown on the GaSb surface with molecular beam epitaxy is examined with atomic force microscopy and high-resolution X-ray diffraction, which show a low RMS roughness of 0.159 nm, a well-controlled two-dimensional growth mode and a full width half maximum of the Bragg diffraction peak of 14.2”, indicating high-quality GaSb wafers. Thus, this work provides useful guidelines for achieving GaSb wafers with high-quality surfaces that show significant promise for substrate applications.